Community conserved areas in Bangladesh : sustainable management strategies - Khan, Mamunul Hoque (Curtin University, 2013)
Community Conserved Areas (CCAs) – fully natural or modified ecosystems consisting of significant biodiversity, providing ecological services and being of considerable cultural importance – are voluntarily looked after by indigenous and local communities through customary laws, traditions or other effective means. Despite the urgent need to protect the natural environment associated with rapid economic and population growth in Bangladesh, conservation and establishing of CCAs are still a relatively new concept for this country.The existing protected area network covers only 1.7% (or 2528.35 km2) of its surface area and the government’s aim is to expand it to 10%. Meeting this target will be meaningless unless there is a new way to assure the adequate protection of such areas in a country that is densely populated. The thesis argues that the ample opportunity to expand the areal extent of protected areas in Bangladesh should be used to include CCAs as part of the National Protected Area System. It describes this as a practical and more effective option to increase nature conservation in a meaningful and effective way.The research is instrumental in introducing the concept of CCA, characterizes different types of CCAs in Bangladesh and identifies associated threats and challenges. Considering the interdependencies between poverty and biodiversity as well as cultural and social values, this study identifies strategies for sustainability of CCAs and biodiversity in Bangladesh.